Factores de éxito en la enseñanza de comprensión lectora en la educación remota de emergencia (ERT) - Salgado Torres, Mariluz (Universidad de Costa Rica, 2022)
The massive closure of schools as a containment measure for COVID-19 forced the adoption of emergency remote education modalities (ERT) during 2020. Despite the relevance of these new education modalities, research around the the conditions that ensure their success in teaching are limited, particularly in Central American countries. The objective of this article was to identify the success factors for the teaching of reading comprehension in emergency remote education modalities in the third grades of three Honduran schools and three Nicaraguan schools, two urban schools and one rural school in Nicaragua; as well as two urban schools and a rural school in Honduras benefited by a non-profit organization during the COVID-19 pandemic. The methodological approach is qualitative-exploratory. The sample is made up of eighteen people from three Honduran schools and three Nicaraguan schools, in addition to seven local experts. The distribution of the sample by country is as follows: 3 teachers, 3 principals, and 4 mothers in Honduras; and 2 teachers, 3 principals, and 4 mothers and 1 father in Nicaragua. Semi-structured interviews and the Delphi method of three interactive rounds were used. The results of this research identified the following success factors: i) emotional and psychological support for teachers and students; ii) instructional design flexible to the heterogeneity of households; iii) facilitation of student-teacher interaction focused on accompaniment; iv) regular communication between teachers and parents; v) parental support from home; vi) trainings for mothers and fathers and vii) trainings for teachers. These findings expand the body of knowledge on ERT and reading comprehension teaching, validating a frame of reference to the realities of Honduras and Nicaragua. For identified success factors with inconclusive findings, further investigation is required. Similarly, future research is important to demonstrate the effect of these success factors in the teaching of reading comprehension in various contexts and realities; as well as analyzing their complex interrelation.